Protective Mechanism of Salvia miltiorrhiza on Carbon Tetrachloride-Induced Acute Hepatotoxicity in Rats - Tzung-Yan Lee; Lee-Ming Mai; Guei-Jane Wang; Jen-Hwey Chiu; Yun-Lian Lin; Han-Chieh Lin (Elsevier, 2003)
The purpose of this study was to investigate the possible mechanisms of Salvia miltiorrhiza (Sm) in carbon tetrachloride (CCl4)-induced acute hepatotoxicity in rats. Male Wistar rats received a single dose of CCl4 (2 ml/kg in corn oil, intraperitoneally). Three hours after CCl4 intoxication, rats received either Sm (100 mg/kg) or silymarin (100 mg/kg) by gastrogavage twice a day for 2 consecutive days. CCl4-induced liver damage was shown by significant elevation of serum aminotransferase levels. Additionally, a significant decrease was observed in hepatic microsomal P450 2E1 protein content and hepatic concentrations of antioxidant enzymes. In contrast, rats given both Sm and silymarin supplement had less elevation of serum aminotransferase concentrations associated with less severe lobular damage of hepatocytes than rats receiving CCl4 alone. Sm administration restored the reduction of hepatic microsomal P450 2E1 protein content as well as inducing an increase in hepatic glutathione concentration. On the other hand, administration of silymarin resulted in an elevation of hepatic superoxide dismutase levels. Moreover, both Sm and silymarin treatment inhibited the elevation of hepatic inducible nitric oxide (iNOS) protein content and nitrite concentration in liver homogenate 24 h after CCl4 intoxication. We concluded that administration of Sm is effective in amelioration of CCl4-induced hepatotoxicity. This effect may be due to its ability to decrease the metabolic activation of CCl4 by an increase in P450 2E1 protein content and its antioxidant activity associated with less increase in hepatic iNOS protein content.